INTERPRETATION OF CRITERIA RELATED TO HUMAN PERSONALITY (International Conference on Economics, Finance, Banking and Management, 2025)
Human personality is a complex, multi-dimensional construct shaped by traits, cognitive interpretations, biological predispositions, and cultural context. Personality criteria serve as benchmarks for understanding individual differences, guiding assessment, and predicting behavior. This article examines the interpretation of criteria related to human personality, integrating trait-based, constructivist, biopsychological, clinical, and cultural perspectives. The findings emphasize that understanding personality requires both measurable traits and interpretive insights shaped by culture and experience.